-2x+7=-3y

4x-6y+4

-2x+7=-3y

solve using elimination

Tutors, sign in to answer this question.

Assuming you mean...

4x-6y = 4

-2x+7=-3y

-2x+7=-3y

Solving by elimination, instead of substitution...

Put x and y on the same side of the second equation

-2x + 3y = -7

Multiply the bottom equation by 2

4x - 6y = 4

2(-2x + 3y) = 2(-7) => -4x +6y = -14

Add both equations together:

0 = -10

No solution.

This is why I posted the comment about you reposting the question.

If you change the -3y you posted into +3y, then of course it works out as Adam posted below.

Thus the reason I posted the comment asking you to verify that you posted the question correctly.

Have a great day.

Have a great day.

Adam P. | Math Tutor for All LevelsMath Tutor for All Levels

4x - 6y =4, solve for x

4x = 4 + 6y

x = 1 + (6/4)y

-2x +7 = 3y

-2(1 +6/4)y) + 7 = 3y (plug in solved value for x)

-2 - 3y +7 = 3y

-6y +5 = 0 (set equal to zero and combine like terms)

-6y = -5

x = 1 + (6/4)(5/6)

x= 1 + 30/24

x = 1 + 1.25

4x - 6y = 4

4(2.25) - 6(5/6) = 4

9 - 5 = 4

-2x + 7 = 3y

-2(2.25) + 7 = 3(5/6)

-4.5 +7 = 2.5

Adam,

When Taylor posted the question,

-2x+7= **-3y**

-2x+7=** 3y**

Already have an account? Log in

By signing up, I agree to Wyzant’s terms of use and privacy policy.

Or

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Your Facebook email address is associated with a Wyzant tutor account. Please use a different email address to create a new student account.

Good news! It looks like you already have an account registered with the email address **you provided**.

It looks like this is your first time here. Welcome!

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Please try again, our system had a problem processing your request.

## Comments